2018
DOI: 10.1021/acs.orglett.8b02204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Enantioenriched Propelladienes and their Application as Ligands in Asymmetric Rh-Catalyzed 1,4-Additions

Abstract: The first synthesis of highly enantioenriched [4.3.3]propelladienes is reported. The novel bridged bicyclo[3.3.0] dienes were applied as steering ligands in the rhodium-catalyzed asymmetric arylation of cyclic enones. The catalytic system showed high catalytic activity, and the 1,4-adducts were obtained in good to excellent yields (46-99%) with enantioselectivities up to 96% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…One of the triallyl derivatives (8 d) has been synthetically transformed by Suzuki-Miyaura crosscoupling reaction to generate the trifluorophenylsubstituted propellane and aza-tricylic derivatives. The structures of RCM products have been confirmed by catalytic hydrogenation and one of the structures (16) was supported by single-crystal X-ray diffraction studies. This methodology may be extended for the synthesis of kopsia indole alkaloids and erythrina alkaloids (Figure 1).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…One of the triallyl derivatives (8 d) has been synthetically transformed by Suzuki-Miyaura crosscoupling reaction to generate the trifluorophenylsubstituted propellane and aza-tricylic derivatives. The structures of RCM products have been confirmed by catalytic hydrogenation and one of the structures (16) was supported by single-crystal X-ray diffraction studies. This methodology may be extended for the synthesis of kopsia indole alkaloids and erythrina alkaloids (Figure 1).…”
Section: Resultsmentioning
confidence: 72%
“…(Scheme 1b). [16] However, to the best of our knowledge, there are no reports on the formation of both scaffolds from a common starting material. This work mainly focuses on the selective formation of propellanes over aza-tricycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis, conformational analysis of the selected ligands 2 a-b, 3 aa-ba, 3 fa and 3 ha was performed using MMFF94 force field, followed by further geometry optimization at the B3LYP/6-31G(d) level. [26] Analysis of 2 a-b revealed that (ap, ap)-, (-sc, ap)-and (-sc, -sc)conformers with alkoxy groups synclinal (sc) and antiperiplanar (ap) to C 4(8) À C 3 (7) bonds are close in energy and thus comparably populated (Figures S2-S3). Steric hindrance imposed even by the smallest exo-substituents, such as methyl groups in 3 aa, is sufficient to significantly affect conformational mobility of the 4,8-endo,endo side chains.…”
Section: Resultsmentioning
confidence: 99%
“…[1] The pioneering reports on the application of bicyclic dienes in the asymmetric rhodium and iridium-catalyzed reactions by Hayashi [2] and Carreira [3] spurred intense research effort directed towards the synthesis and study of novel steering ligands. A variety of structurally diverse dienes based on bicyclo [2.2.1]heptadiene, [2,4] bicyclo [2.2.2]octadiene, [3,4c,5] bicyclo [3.3.0]octadiene [6] and propelladiene, [7] bicyclo [3.3.1]nonadiene, [8,9] dicyclopentadiene, [10] cyclooctadiene, [11] as well as acyclic [12] frameworks have been developed. Ligands of this type have been found to be particularly effective in the asymmetric rhodium-catalyzed conjugate addition of boronic acids to α,β-unsaturated carbonyl compounds and arylation of imines.…”
Section: Introductionmentioning
confidence: 99%